2022
DOI: 10.1097/hcr.0000000000000717
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between a Second Course of Cardiac Rehabilitation and Cardiovascular Outcomes Following Repeat Percutaneous Coronary Intervention Events

Abstract: Although evidence supports cardiac rehabilitation (CR) after an initial coronary artery disease (CAD) event, it is unclear whether a repeat course of CR (CR × 2) is beneficial after a recurrent CAD event. We found that among individuals who had previously participated in CR after an initial PCI, CR × 2 was associated with improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our recent clinical study showed that exercise-based cardiac rehabilitation significantly prevented cardiovascular death and recurrent heart attack ( 10 ). In addition, recent preclinical studies from our team investigated drug ( 11 , 12 ) and non-drug ( 11 13 ) preconditioning strategies to ameliorate muscle damage caused by fatal stress induced by exhaustive exercise in non-obese mice.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent clinical study showed that exercise-based cardiac rehabilitation significantly prevented cardiovascular death and recurrent heart attack ( 10 ). In addition, recent preclinical studies from our team investigated drug ( 11 , 12 ) and non-drug ( 11 13 ) preconditioning strategies to ameliorate muscle damage caused by fatal stress induced by exhaustive exercise in non-obese mice.…”
Section: Introductionmentioning
confidence: 99%